Engineering properties of composite materials containing waste ceramic dust from advanced hollow brick production as a partial replacement of Portland cement. (July 2016) - Kulovaná, Tereza; Vejmelková, Eva; Pokorný, Jaroslav; Siddique, Jamal Akhter; Keppert, Martin; Rovnaníková, Pavla; Ondráček, Michal; Keršner, Zbyněk; Černý, Robert
Waste ceramic dust originating in the advanced hollow brick production is applied as a supplementary cementing material replacing a part of Portland cement in concrete. The measurements of mechanical and fracture-mechanical properties, water vapor and liquid water transport parameters, thermal conductivity, specific heat capacity, and freeze/thaw resistance show that the ceramic dust application does not affect negatively the properties of the analyzed concretes over the whole studied Portland cement replacement range up to 40% by mass. The achievement of such a high limit for the ceramic dust application can be attributed, besides the pozzolanic reaction being initiated already during the time period of 7 to 28 days, to the positive effect of the excess ceramic dust in the mixes with a high volume of uniformly distributed air voids. The part of the ceramic additive which cannot participate in the hydration and pozzolanic reactions due to the lack of available Ca 2+ acts, apparently, as fine aggregate partially filling the voids, thus contributing to the compaction of the hardened mixes and compensating, to a certain extent, the factual decrease of the amount of binder.